Susceptibility of different serovars of Chlamydia trachomatis to inactivation by normal human serum. Issue 4 (August 1985) - Osborn, M F; Johnson, A P; Taylor-Robinson, D
Abstract : The ability of a panel of normal human serum samples to inactivate 12 strains of Chlamydia trachomatis, each of a different serovar, was investigated. A wide range of antichlamydial activity was observed, with survival rates of C trachomatis varying from less than 1% in some experiments to 100% in others. The strain specificity of the anti-chlamydial activity exhibited by individual serum samples was not, however, related to the antigenic cross reactivity between serovars demonstrable by microimmunofluorescence testing, which suggested that type specific antigens were not predominantly involved in the inactivation process.